(untitled) (Journal of Information Technology and Digital World, 2021)
Waiting for anything is undesirable by most of the human beings. Especially in the case of digital money transactions, most of the people may have doubtful thoughts on their mind about the success rate of their transactions while taking a longer processing time. The Unified Payment Interface (UPI) system was developed in India for minimizing the typographic works during the digital money transaction process. The UPI system has a separate UPI identification number of each individual consisting of their name, bank name, branch name, and account number. Therefore, sharing of account information has become easier and it reduces the chances of typographic errors in digital transaction applications. Sharing of UPI details are also made easy and secure with Quick Response (QR) code scanning methods. However, a digital transaction like UPI requires a lot of servers to be operated for a single transaction same as in National Electronic Fund Transfer (NEFT) and Immediate Payment Services (IMPS) in India. This increases the waiting time of digital transactions due to poor server communication and higher volume of payment requests on a particular server. The motive of the proposed work is to minimize the server communications by employing a distributed blockchain system. The performance is verified with a simulation experiment on BlockSim simulator in terms of transaction success rate and processing time over the traditional systems.